1999
DOI: 10.1274/jmor.16.23
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Lectins to the Zona Pellucida of In Vitro Matured Pig Oocytes and Sperm-Oocyte Interaction In Vitro.

Abstract: Immature pig oocytes cultured for 36 h in a modified tissue culture medium 199B were freed from cumulus cells and treated for 30 min with fluorescein isothiocyanate-labelled lectins. When examined under fluorescence illumination, Ricinus communis agglutinin (RCA-I) and Lens culinaris agglutinin (LCA) bound to all oocytes, with the strongest fluorescence in either the outer region of the ZP (RCA-I) or throughout the ZP (LCA). However, Bandeiraea simplicifolia lectin-I (BS-I) and Ulex europaeus agglutinin-I (UEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Although it has been reported that pig spermatozoa which initially bind to the ZP have intact plasma membrane [30][31][32], the present results indicate that, in the pig, only spermatozoa undergoing or completing acrosome reaction could bind firmly to the ZP as suggested by Jones et al [33]. However, it is unclear at present how α-L-fucosidase might be involved in binding of spermatozoa to the ZP because it has been shown that fucose residues are present only in the inner region of the ZP [23]. It has been reported in mice that α-galactosyl residues which are present in the inner region of the ZP [34] also play a role as a sperm receptor [35].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Although it has been reported that pig spermatozoa which initially bind to the ZP have intact plasma membrane [30][31][32], the present results indicate that, in the pig, only spermatozoa undergoing or completing acrosome reaction could bind firmly to the ZP as suggested by Jones et al [33]. However, it is unclear at present how α-L-fucosidase might be involved in binding of spermatozoa to the ZP because it has been shown that fucose residues are present only in the inner region of the ZP [23]. It has been reported in mice that α-galactosyl residues which are present in the inner region of the ZP [34] also play a role as a sperm receptor [35].…”
Section: Discussionsupporting
confidence: 49%
“…It is known that the penetration of spermatozoa through the ZP may be facilitated by hydrolytic enzymes released from the acrosome (for review see [36]). Furthermore, it has been shown that abundant Man and Gal residues are present throughout the ZP and in the outer region of the ZP, respectively, while Fuc residues are found only in the inner region of the ZP in pig oocytes [23]. Therefore, it is possible that α-L-fucosidase, α-Dmannosidase and β-D-galactosidase are all involved in zona penetration of spermatozoa and that each glycosidase plays a role in the different regions of the ZP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucose has been detected in the porcine ZP using Ulex europaeus agglutinin 1 (UEA-I) lectin histochemistry (Song et al, 1999;Pastor et al, Pattern A showed significant differences, with higher values observed in the control group (54.7 ± 1.6%) than in the TALP (15.1 ± 1.2%) and TALP + E (12.2 ± 1.1%) groups (P < 0.001); pattern B showed higher values in the TALP group (61.8 ± 1.6%) than in the TALP + E (35.2 ± 1.6%) and control (43.2 ± 1.6%) groups (P < 0.01); pattern C showed significant differences (P < 0.001), with maximum values observed in the TALP + E group (52.5 ± 1.7%) compared with the TALP (23.1 ± 1.4%) and control (2.1 ± 0.5%) groups. Different letters indicate significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…It shows maximum activity in pig OF close to the moment of ovulation (Carrasco et al, 2008b). Its substrate, fucose, has been detected in sugar chains on the spermatozoal surface in the mouse (Boldt et al, 1989), bull (Taitzoglou et al, 2007) and boar (Jiménez et al, 2003), and also on the inner region of the ZP in pigs (Song et al, 1999). In addition, when carbohydrate involvement in spermatozoaegg interactions were studied by adding sugars to fertilisation media, fucose and the polysaccharide fucoidan induced a significant drop in penetration rates in cattle (Tanghe et al, 2004) and pigs (Töpfer-Petersen et al, 1985;Song et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%